DESKTOP REMOTE CONTROL SYSTEM - Francis, Chan Yong Lun (Universiti Malaysia Sarawak, (UNIMAS), 2005)
Desktop Remote Control System is a system that enables a 56MHz radio frequency remote control toy car to be maneuvered via a desktop computer terminal. This system allows user to control the remote control toy car by using a mouse click or keyboard functions. The development of the desktop remote control system involves hardware interface and software interface design. The hardware interface is used to interconnect the 56MHz radio frequency remote control toy car transmitter to a desktop computer parallel port. The hardware interface is built using relays, parallel port printer cable, connection wires and printed circuit board. The software interface is used as a controlling interface aiming to maneuver the remote control toy car which will be displayed on a monitor screen. The software interface is developed using Java language under Windows XP environment. A kernel mode driver is used to enable the software interface to control desktop computer parallel port in Windows XP environment. Desktop remote control system can be fwrther extended to become a useful tool in the area of research as well as remote control surveillance field in the future.